The mediating influence of internal accountability systems on teachers' assessment practices - Hay, Aletha Adell (University of Ottawa (Canada), 2005)
This collective case study explores the nature of internal accountability systems in two elementary schools situated within a provincial-level accountability agenda using large-scale performance testing to ensure both school accountability and professional learning. The purpose of this mixed model study was threefold: first, to explore the components and strength of internal accountability systems and the interactive dynamics with the external system; second, to identify key environmental factors that impacted the school-based systems; and third, to reveal the influence these internal forums had on teachers' assessment practices. Multiple theoretical lenses informed the conceptual framework used to analyze the policy to practice connections in the restructuring educational system. The study findings reveal several observations. First, internal accountability systems should possess five components including aims, information on school performance, a standard of achievement, person(s) who judge school performance, and mechanisms to guide and monitor teachers' practices. The presence of all five components suggests that strong internal accountability systems were in place in the two schools. Second, two environmental factors impacting these systems were large-scale performance tests and professional leadership. There is indication that the design of the testing program minimized unintended negative effects linked with public reports and that school leadership was instrumental in mobilizing support for school improvement and professional learning. Third, the study also describes the relationship between the internal and external systems nested within the province's standards-based reform initiative. The findings unpack the compatibility between the instruments and strategies of the school-level systems and those of the state-level system, lending support for the proposition that external oversight contributes to school-based ownership for proactive change. Finally, the study findings illuminate how internal accountability systems mediated teachers' practices and supported the development of collegial assessment practices. The findings lend support for the position that the dual aims of accountability and professional learning are enabled when internal accountability systems are facilitated by a professionally oriented external policy environment.
Keywords: Education, Administration.; Education, Elementary.